Discovering, Characterizing, and Applying Acyl Homoserine Lactone-Quenching Enzymes to Mitigate Microbe-Associated Problems Under Saline Conditions - Wang, Tian-Nyu; Guan, Qing-Tian; Pain, Arnab; Kaksonen, Anna H.; Hong, Pei-Ying (Frontiers in Microbiology, 2019)
Quorum quenching (QQ) is proposed as a new strategy for mitigating microbe-associated problems (e.g., fouling, biocorrosion). However, most QQ agents reported to date have not been evaluated for their quenching efficacies under conditions representative of seawater desalination plants, cooling towers or marine aquaculture. In this study, bacterial strains were isolated from Saudi Arabian coastal environments and screened for acyl homoserine lactone (AHL)-quenching activities. Five AHL quenching bacterial isolates from the genera Pseudoalteromonas, Pontibacillus and Altererythrobacter exhibited high AHL-quenching activity at a salinity level of 58 g/L and a pH of 7.8 at 50 °C. This result demonstrates the potential use of these QQ bacteria in mitigating microbe-associated problems under saline and alkaline conditions at high (>37 °C) temperatures. Further characterizations of the QQ efficacies revealed two bacterial isolates, namely, Pseudoalteromonas sp. L11 and Altererythrobacter sp. S1-5, which could possess enzymatic QQ activity. The genome sequences of L11 and S1-5 with a homologous screening against reported AHL quenching genes suggest the existence of four possible QQ coding genes in each strain. Specifically, two novel AHL enzymes, AiiAS1-5 and EstS1-5 from Altererythrobacter sp. S1-5, both contain signal peptides and exhibit QQ activity over a broad range of pH, salinity and temperature values. In particular, AiiAS1-5 demonstrated activity against a wide spectrum of AHL molecules. When tested against three bacterial species, namely, Aeromonas hydrophila, Pseudomonas aeruginosa and Vibrio alginolyticus, AiiAS1-5 was able to inhibit the motility of all three species under saline conditions. The biofilm formation associated with P. aeruginosa was also significantly inhibited by AiiAS1-5. AiiAS1-5 also reduced the quorum sensing-mediated virulence traits of A. hydrophila, P. aeruginosa and V. alginolyticus during the mid and late exponential phases of cell growth. The enzyme did not impose any detrimental effects on cell growth, suggesting a lower potential for the target bacterium to develop resistance over long-term exposure. Overall, this study suggested that some QQ enzymes obtained from the bacteria that inhabit saline environments under high temperatures have potential applications in the mitigation of microbe-associated problems.